Comparing the Effectiveness of Iqro’ and Tsaqifa Methods on Elderly Qur’anic Reading Skills at Nurul Iman Karanganyar : Perbandingan Efektivitas Metode Iqro’ dan Tsaqifa terhadap Kemampuan Membaca Al-Qur’an Lansia di Nurul Iman Karanganyar - Amy Lia Laili (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2025)
Abstract Purpose – This study aims to compare the effectiveness of the Iqro’ and Tsaqifa methods in improving the Qur'anic reading ability among elderly women at the Nurul Iman Islamic Boarding School for the Elderly in Karanganyar. The research is grounded in the reality that cognitive decline commonly occurs with advancing age, making the selection of an appropriate instructional method a critical factor in enhancing learning outcomes and spiritual motivation among elderly learners. Design/methods/approach – A quantitative approach was employed using a quasi-experimental design. The sample consisted of 54 elderly female learners, divided into two groups: the Iqro’ method group (n=28) and the Tsaqifa method group (n=26). Data were collected through an oral reading test of Surah Al-Mulk verses 1–5 and analyzed using an independent sample t-test, following tests for normality and homogeneity of variance. Findings – The results indicate that the Tsaqifa group achieved a higher mean score (59.27) compared to the Iqro’ group (53.75). Furthermore, the percentage of participants categorized as “very good” was higher in the Tsaqifa group (34.62%) than in the Iqro’ group (21.43%). The t-test revealed a statistically significant difference between the two methods (t = 2.253 > t₀.05 = 2.006; p < 0.05), indicating that the Tsaqifa method is more effective in enhancing Qur'anic reading skills among elderly learners. Research implications/limitations – The study offers practical insights for Islamic educational institutions and Qur’an instructors in selecting pedagogical methods tailored to elderly learners. It also enriches the discourse on age-sensitive Qur’anic instruction methods. However, the study is limited by its scope, being conducted in a single pesantren and involving only female participants. Originality/value – This study presents a novel contribution by quantitatively comparing two widely used Qur’anic reading methods among elderly learners—an area that has received limited scholarly attention within Islamic education research. The findings may inform curriculum development and teacher training programs based on andragogical principles and spiritual literacy for aging populations. Abstrak Tujuan – Penelitian ini bertujuan untuk membandingkan efektivitas metode Iqro’ dan Tsaqifa terhadap kemampuan membaca Al-Qur’an pada lansia perempuan di Pondok Pesantren Lansia Nurul Iman, Karanganyar. Penelitian ini dilatarbelakangi oleh kenyataan bahwa pada usia lanjut terjadi penurunan fungsi kognitif, sehingga pemilihan metode pembelajaran yang tepat menjadi faktor penting dalam meningkatkan hasil belajar dan motivasi spiritual lansia. Desain/Metode/Pendekatan – Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksperimen semu (quasi-experimental). Sampel penelitian terdiri dari 54 orang lansia perempuan yang dibagi ke dalam dua kelompok: kelompok metode Iqro’ (n=28) dan kelompok metode Tsaqifa (n=26). Data dikumpulkan melalui tes membaca lisan Surah Al-Mulk ayat 1–5 dan dianalisis menggunakan uji-t (independent sample t-test) setelah uji asumsi normalitas dan homogenitas terpenuhi. Temuan – Hasil penelitian menunjukkan bahwa kelompok Tsaqifa memperoleh rata-rata skor lebih tinggi (59,27) dibanding kelompok Iqro’ (53,75). Persentase kategori